The "most beautiful place" where "it's not possible to live": a qualitative study of relational well-being in an area of climate vulnerability, Bangladesh - Lilier, Kyra; Dalglish, Sarah L.; Reñosa, Mark Donald; Selim, Samiya A.; Raihan, Syed Tauheed; Islam, Rafia; Das, Jennifer; Danquah, Ina; Sauerborn, Rainer; Bärnighausen, Kate (PLOS ONE, 2025)
Purpose Climate change is the greatest global health threat of the 21st century, but little is known about well-being in climate vulnerable populations. We investigate how well-being is shaped by common and unique stressors in an area of climate vulnerability in Bangladesh. Methods We present findings from 60 semi-structured in-depth interviews. We inductively analyzed our data following a Reflexive Thematic Analysis approach and then applied a Relational Well-being (RWB) framework. Results We found that well-being was influenced negatively by factors such as financial worries, forced migration, social pressure, and natural disasters. Well-being was influenced positively by factors such as financial satisfaction, voluntary migration, social support, and place attachment. Conclusions Using relational well-being as a conceptual lens allowed us to explore the dynamism and complexity of factors shaping well-being that were partly specific to the local context and partly rooted in wider societal and global structures. Policies which aim to improve the well-being of climate vulnerable populations should consider relational well-being as a conceptual tool to leverage locally available informal resources, such as suppotive reciprocal relationships.